Beat perception and synchronization abilities in young children - Einarson, Kathleen M. (My University, 2017)
Even without formal training, adults can easily perceive, clap, tap, and move in time to a musical beat, but these behaviours are more difficult for children and the development of these abilities in childhood is not well understood. Until the present thesis, there were no developmentally appropriate tasks to separately assess musical beat perception and beat synchronization in children. In Chapter 2, I created a child friendly video judgment task to assess beat perception in the context of both simple and complex musical timing, and demonstrated that five-year-old children’s ability to perceive both tempo- and phase-driven beat misalignments is affected by metric complexity. In Chapter 3, I again used the complex Beat Alignment Task (cBAT) to show that the detection of beat misalignment is not significantly affected by the inclusion of dynamic video stimuli compared to static images. Chapter 4 expanded the perception task by adding a tapping synchronization component, and tested both five- and seven-year-old children. The complex Beat Alignment and Tapping Task (cBATT) showed that although children’s overall perceptual sensitivity improves with age, the perceptual bias for simple structures persists. However, although children were significantly better at tapping to metronomes than to songs, musical tapping synchronization was not obviously affected by metric complexity. Instead, performance related to other acoustic characteristics of the music, such as spectral flux, energy, and density. Together, these findings suggest that musically untrained children are sensitive to phase and tempo information in a perception-only task, and show perceptual specialization for culturally typical musical metres, but this is not the case for production. Thus, beat synchronization ability appears to be somewhat dissociated from beat perception in children. These studies represent the first use of a developmentally appropriate task to separately assess children’s beat perception and synchronization while also examining the role of metre and early experience.
Keywords: music, child development, entrainment, meter, enculturation, synchronization